Impacto da tensão trativa adotada no dimensionamento de rede coletora de esgoto sanitário sobre os seus custos construtivos - Souza, Gracielle Ferreira de (2021)
In Brazil, there is a deficit in sewage collection and treatment services and for the universalization of sewage systems, investments in infrastructure are essential. However, one of the main obstacles to the expansion of the sewage system in the country is the high cost of implementing the sewage collection network. A design parameter that can influence the costs of the sewage collection network is the shear stress. In this sense, this research aims to analyze the effects of the adoption of minimum values of tension for the dimensioning of the sewage collection network on the associated costs for various topographic scenarios. For the purpose of study, with the aid of the CEsg software, 50 scenarios were designed, with identical traces of the collecting network and with different configurations of topography and minimum shear stress. The results indicated that the diameter of the collectors remained constant with the variation of the tensile stress, reaching the minimum value of 150 mm and that there is no difference in cost between the 0.6 and 1.0 Pa shear stresses for all the studied scenarios. It was found that from the 1.0 Pa shear tension, the cost increased with the increase in the tractive tension adopted in the project, and for more rugged áreas, the increase in cost was expressed as negligible. In general, it was found that the shear tension and the topography play determinant roles in the cost, the higher the value of the tension and the lower the slope of the topography, the greater the cost of implementing the sewage collection network. However, in terrains with steeper topographies, the use of shear tension higher than that suggested by the standard is allowed, in more than 3.0 Pa, with a minimum incidence of additional costs in relation to the value of 0.6 Pa or 1,0 Pa.